EVALUATION OF KNOWLEDGE, ATTITUDE, AND PRACTICES AMONG HYPOTHYROID FEMALE PATIENTS IN A TERTIARY CARE HOSPITAL - MUFIDA BEGUM I; KUMUDHA D (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Hypothyroidism is the most prevalent thyroid disorder globally. Women are more likely to have thyroid disorders than men. There is a dearth of data on Indian women with hypothyroidism regarding their knowledge, attitude, and practices (KAP). Therefore, this study aimed to evaluate Indian hypothyroid women based on their KAP. Methods: Hypothyroid women who are ≥18 years old participated in the study. It was planned to be carried out in a tertiary care hospital, in South India. This strategic cross sectional study was assessed using the KAP-33 questionnaire. Results: The present study showed that age <30 years was predominant and was associated with a significant effect (p<0.01) on knowledge, attitude, and practice. Knowledge level was not significantly associated with scholastic level (p>0.05), work status (p>0.05), or region (p>0.05). Age and marital status were strongly associated with the level of KAP about hypothyroidism, and the family history of thyroid disorder, occupational status, area of living, and number of comorbidities were significantly associated with the level of attitude and practice and non-significant association with knowledge. Educational level showed no significant association with knowledge, attitude, and practice regarding hypothyroidism. Conclusion: Educated patients surprisingly found that they lacked knowledge regarding thyroid disorders, and younger women (<30 years) had more knowledge about hypothyroidism.